Prospective parenting: sexual identity and intercultural trajectories. Issue 7 (3rd July 2019) - Leal, Daniela; Gato, Jorge; Tasker, Fiona
Abstract: This study explored the impact of sexual identity on attitudes towards parenthood among childless individuals from Portugal and the United Kingdom (UK). Compared to heterosexuals, lesbians, gay men and bisexuals were less likely to: desire and intend to have children, be concerned about the prospect of childlessness or perceive children as a source of enrichment. They also anticipated more stigma as parents than did heterosexuals. Compared to UK participants, all Portuguese participants, independent of sexual identity, desired and intended more to have children, were more concerned about childlessness, reported higher levels of parental commitment, anticipated less stigma and expected more social support as parents. Portuguese lesbian, gay and bisexual participants expressed greater desire to have children than did those in the UK. Only in the UK did lesbian, gay and bisexual participants perceive children less as a source of enrichment than did heterosexuals and anticipate negative costs associated with parenting. We concluded that the intersectional influence of different cultural climates on parenting aspirations should be taken into account in future research alongside sexual identity.